2002
DOI: 10.1093/annonc/mdf089
|View full text |Cite
|
Sign up to set email alerts
|

First-line oral capecitabine therapy in metastatic colorectal cancer: a favorable safety profile compared with intravenous5-fluorouracil/leucovorin

Abstract: Capecitabine is at least as effective, better tolerated and more convenient than i.v. 5-FU/leucovorin as treatment for patients with metastatic colorectal cancer. Analysis of data from two large phase III trials demonstrates that efficacy is not compromised in patients requiring a dose reduction for adverse events. The phase III data and an additional pharmacokinetic study support a lower starting dose in patients with moderate renal impairment at baseline (calculated creatinine clearance 30-50 ml/min) and a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
252
11
9

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 477 publications
(291 citation statements)
references
References 9 publications
19
252
11
9
Order By: Relevance
“…Over the past 10 years, there has been an increasing use of capecitabine monotherapy and capecitabine-based combination regimens in the treatment of mCRC, which has been due, in large part, to the convenience and increased patient preferences for oral chemotherapy [5054]. Randomized studies have shown that capecitabine-based treatments are associated with equal clinical efficacy and reduced toxicities when compared to infusional 5-FU regimens [5054].…”
Section: -Fu Tdm With Capecitabinementioning
confidence: 99%
See 1 more Smart Citation
“…Over the past 10 years, there has been an increasing use of capecitabine monotherapy and capecitabine-based combination regimens in the treatment of mCRC, which has been due, in large part, to the convenience and increased patient preferences for oral chemotherapy [5054]. Randomized studies have shown that capecitabine-based treatments are associated with equal clinical efficacy and reduced toxicities when compared to infusional 5-FU regimens [5054].…”
Section: -Fu Tdm With Capecitabinementioning
confidence: 99%
“…Randomized studies have shown that capecitabine-based treatments are associated with equal clinical efficacy and reduced toxicities when compared to infusional 5-FU regimens [5054]. Finally, several pharmacoeconomic studies have demonstrated that capecitabine-based chemotherapy is associated with significant cost savings when compared to infusional 5-FU chemotherapy, and these economic benefits are seen for the adjuvant therapy setting as well as for the treatment of metastatic disease [5559].…”
Section: -Fu Tdm With Capecitabinementioning
confidence: 99%
“…This likely reflects the variable metabolism of capecitabine-dose adjustment may functionally adjust exposure to biologically appropriate doses. Standard recommendations in the capecitabine package insert [20] are identical to those in the aforementioned trial and will be followed; these are recapitulated in table 4. Table 5 provides suggestion on dosereductions for specific toxicities.…”
Section: Capecitabinementioning
confidence: 99%
“…The tablets are supplied as biconvex, oblong film-coated tablets. Each tablet is light peach colored tablet contains 150mg of capecitabine and each peach-colored tablet contains 500mg [20].…”
Section: Version 3/8/2011mentioning
confidence: 99%
See 1 more Smart Citation